Posted by **Allison** on Sunday, October 2, 2011 at 7:20pm.

Let f(x)=x^2+5x-3.

Find f′(x) and find f′(1).

- Calculus -
**Allie**, Sunday, October 2, 2011 at 7:21pm
f'= 2x+5

F'(1) is 7

- Calculus -
**Allison**, Sunday, October 2, 2011 at 7:23pm
thanks allie but i need someone to show the work to how they got those answers too please :)

- Calculus -
**Ed**, Sunday, October 2, 2011 at 8:42pm
She found the derivative of the equation, and then simply plugged in a one for the (x) after it was in its derivative form.

- Calculus -
**Allison**, Sunday, October 2, 2011 at 9:21pm
yes I know that but I need to steps for how you find the derivative.

- Calculus -
**Steve**, Monday, October 3, 2011 at 5:52am
basically just the power rule:

y = x^n

y' = n*x^(n-1)

## Answer This Question

## Related Questions

- Calculus - A table of values for f,g,f′, and g′ are given in the ...
- Calculus - A table of values for f,g,f′, and g′ are given in the ...
- Calculus - Find the x-coordinates of any relative extrema and inflection point(s...
- College Physics - Use the relativistic coordinate transformation (x, y, z, t) &#...
- PHY 2054 - Use the relativistic coordinate transformation (x, y, z, t) − (...
- Math- Calc - Suppose f(5)=5, f′(5)=5, g(5)=8, g′(5)=−8, and H(...
- physics - Consider the two observers O and O′ at the origins of the ...
- Calculus 1 - Find the requested derivative using limits a. 𝑓′(-4)...
- Math- Calc - Suppose F(G(x))=x^(2) and G′(1)=5. Find F′(G(1)). F&#...
- Math - Suppose F(G(x))=x^(2) and G′(1)=5. Find F′(G(1)). F′(G(...

More Related Questions